2005
DOI: 10.1111/j.1365-2710.2005.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of doxorubicin combined with RadioselectanR, a contrast agent, for chemoembolization

Abstract: Doxorubicin combined with Radioselectan stored at room temperature is stable for 48 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This is an important point of note given some of the alternate methodologies deployed in the literature and the conclusions drawn as a result. Stability data taken from previous studies 34,35 show that DOX is chemically broken down when stored in aqueous solutions. Mayer et al 34 observed a loss of 60% of the original DOX concentration for solutions stored at 37 C for 140 h in normal saline and Ioversol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an important point of note given some of the alternate methodologies deployed in the literature and the conclusions drawn as a result. Stability data taken from previous studies 34,35 show that DOX is chemically broken down when stored in aqueous solutions. Mayer et al 34 observed a loss of 60% of the original DOX concentration for solutions stored at 37 C for 140 h in normal saline and Ioversol.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, a loss of approximately 70% of the original DOX concentration for solutions stored at 40 C for 168 h in water and Radioselectan Õ was reported. 35 In the current study, it was expected that extracts derived from the 1.4 wt% loaded RC-DEBs at the 168 h elution time point, which had the highest DOX concentration of 2.3 lg/mL in the cell culture media, would have the lowest cell viability. Instead, all DOX-containing extracts at 168 h exhibited similar cell viabilities between 85 and 79%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough literature survey has indicated several HPLC methods for the determination of erlotinib·HCl in pharmaceutical formulations as well as in biological fluids using ultra-violet and mass spectra detection. [3][4][5][6][7][8] The HPLC method was developed for the assay of erlotinib in the presence of degradation products. 9 The analysis of erlotinib and its metabolites is conducted in rat tissue sections by MALDI quadrupole time-of-flight mass.…”
Section: Erlotinibmentioning
confidence: 99%